Purification and subunit composition of acetohydroxyacid synthase I from Escherichia coli K-12. - Eoyang, L (1984)
Acetohydroxyacid synthase I from Escherichia coli K-12 has been purified to near homogeneity. Analysis of the purified enzyme by sodium dodecyl sulfate-polyacrylamide gel electrophoresis showed the presence of two polypeptides, one with a molecular weight of 60,000 and one with a molecular weight of 9,500. These two polypeptides were present in constant proportion to each other and to enzyme activity. The molar ratio of the two polypeptides (Mr 9,500:60,000), estimated from stained polyacrylamide gels, was 1. Antisera raised against the 60,000 Mr polypeptide precipitated both the 60,000 and the 9,500 Mr polypeptides from extracts of cells labeled with [35S]methionine. The addition of sodium dodecyl sulfate before immunoprecipitation eliminated the smaller polypeptide, and only the larger one was recovered. The hydrodynamic properties of the native enzyme confirmed a previous report that the largest enzymatically active species has a molecular weight of about 200,000; this species contains both the 60,000- and 9,500-molecular-weight polypeptides.